The Influence of Artificial Intelligence Technology in Automotive and Consumer Brand Engagement on E-Word-of-Mouth - Phalalert, Decha (Journal for Strategy and Enterprise Competitiveness, 2024)
The goals of this study are to study the influence of factors affecting electronic word-of-mouth communication among consumers. The concepts of Artificial Intelligence quality, enjoyment, novel experiences, and consumer brand engagement are applied in this research. 488 participants were collected by using a stratified sampling method. Results from ordered logistic regression analysis model. The Artificial Intelligence quality , novel experiences and consumer brand engagement have a significant positive influence on electronic word-of-mouth.